2021
DOI: 10.1128/mbio.02683-20
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc Finger Antiviral Protein ZAP Restricts Human Cytomegalovirus and Selectively Binds and Destabilizes Viral UL4 / UL5 Transcripts

Abstract: Interferon-stimulated gene products (ISGs) play a crucial role in early infection control. The ISG zinc finger CCCH-type antiviral protein 1 (ZAP/ZC3HAV1) antagonizes several RNA viruses by binding to CG-rich RNA sequences, whereas its effect on DNA viruses is less well understood. Here, we decipher the role of ZAP in the context of human cytomegalovirus (HCMV) infection, a β-herpesvirus that is associated with high morbidity in immunosuppressed individuals and newborns. We show that expression of the two majo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 85 publications
10
49
0
Order By: Relevance
“…Recently, we identified ZAP and TRIM25 as host restriction factors against HCMV using an arrayed interferon-stimulated gene expression screen, the first such screen against a herpesvirus [ 34 ]. These results were later confirmed by an independent study that showed CRISPR Cas9 deletion of ZAP increased HCMV replication and that ZAP targeted transcripts from the UL4-UL6 region of the virus [ 33 ].…”
Section: Cpg Profiles Of Herpesvirusesmentioning
confidence: 71%
See 2 more Smart Citations
“…Recently, we identified ZAP and TRIM25 as host restriction factors against HCMV using an arrayed interferon-stimulated gene expression screen, the first such screen against a herpesvirus [ 34 ]. These results were later confirmed by an independent study that showed CRISPR Cas9 deletion of ZAP increased HCMV replication and that ZAP targeted transcripts from the UL4-UL6 region of the virus [ 33 ].…”
Section: Cpg Profiles Of Herpesvirusesmentioning
confidence: 71%
“…More recently, we and others have shown that ZAP can restrict the replication of large DNA viruses. Disruption of ZAP increases replication of the herpesvirus HCMV and the poxvirus vaccinia [ 33 , 34 , 35 ]. In the case of the vaccinia virus, the viral C16 protein was shown to antagonise ZAP antiviral activity by relocalising ZAP to punctate cytoplasmic structures.…”
Section: Zinc Finger Antiviral Protein (Zap)mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutating Y108 partially decreased ZAP-L antiviral activity for SARS-CoV-2, which could indicate that ZAP interacts with other motifs in the viral RNA in addition to CpGs. While it is clear that ZAP binds CpG dinucleotides in the context of single-stranded RNA, how the surrounding sequence and structural context of the CpG affect ZAP binding and antiviral activity as well as the role for non-CpG binding sites in viral RNA is still unclear [ 6 , 14 , 18 20 , 30 , 33 , 35 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there has been substantial progress in understanding how ZAP restricts viral replication, several key questions remain. First, the specific contribution of ZAP binding to CpGs for viral restriction is unclear, especially since ZAP can also restrict viruses with increased UpA abundance and CpG abundance does not always predict ZAP-sensitivity [ 14 , 15 , 30 , 39 , 40 ]. Second, while ZAP-L is often more antiviral than ZAP-S, depending on the experimental system and virus being studied, the specific determinants in the PARP domain that lead to increased antiviral activity and how this correlates with interactions between ZAP and cofactors remains to be resolved.…”
Section: Introductionmentioning
confidence: 99%